Study of Butterfly Diversity in Botanical Garden Indonesia - Murwitaningsih, Susanti; Setyaningsih, Maryanti; Nisa, Ranti An; Nurlaeni, Yati (International Journal of Psychosocial Rehabilitation, 2020)
The diversity and the number of butterflies decrease every year due to various environmental factors and unscientific management of natural resources. This study is focused on the assessment of diversity, abundance and uniformity, as well as the dominance of butterfly species in relation to vegetation composition in a habitat. In this study, we also investigate the factors that affect the life of butterfly species in the Cibodas Botanical Garden, Indonesia. This report reflects the common condition of botanical gardens in Indonesia, which function as a conservation garden while their surrounding areas are quickly being converted to make way for property and industrial development. We use catch and release technique for sampling over a period of three months in four different types of locations. From May to July 2018, we recorded as many as 885 butterflies (33 species) from five families. Our assessment of diversity shows that the waterfall location had the most diversity of species (H = 2.44), with a high abundance (R) and was the most balanced (E) with an index of 4.647 and 0.749 respectively. Delias belisama and Ypthima pondacus were two species that were the most dominant in numbers. The butterfly species that were observed generally preferred a humid area with varied vegetation, such as the Ciismun Waterfall. Our study shows that a high variety of vegetation and humidity in habitat, as well as its proximity to residential areas, have a significant correlation to the diversity of the butterfly species in a habitat.